2020
DOI: 10.1101/2020.08.15.20175067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pilot study to see any Change of the Nasal and Oropharyngeal Microbiota with Prolonged Use of Medical Masks during the COVID-19 Outbreak

Abstract: Background: The outbreak of coronavirus disease 2019 (COVID-19) has played havoc on the healthcare system and society. Many international guidelines have put forward various measures to control the spread and, using various quality masks seems to be the most important amongst them. This was a cross-sectional pilot study to see any alterations in the bacterial flora of the nasal and the oropharyngeal (OP) microbiota with the use of medical masks over prolonged periods during this COVID-19 outbreak. Methods: Nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The ages of the infected patients ranged from 10 to 80 years, in which the highest number of isolated bacterial and fungal species was within the age groups 50-60 years and the lowest was in the groups 70 years and over. The results showed that the infection rate of Gram-positive bacteria was low, and this is due to the natural presence of most Gram-positive bacteria such as Staphylococcus & Streptococcus, a normal flora in the upper respiratory tract, and these results were consistent with (Roy et al, 2020).…”
Section: Relationship Of Age To Bacterial Infections and Yeastssupporting
confidence: 67%
“…The ages of the infected patients ranged from 10 to 80 years, in which the highest number of isolated bacterial and fungal species was within the age groups 50-60 years and the lowest was in the groups 70 years and over. The results showed that the infection rate of Gram-positive bacteria was low, and this is due to the natural presence of most Gram-positive bacteria such as Staphylococcus & Streptococcus, a normal flora in the upper respiratory tract, and these results were consistent with (Roy et al, 2020).…”
Section: Relationship Of Age To Bacterial Infections and Yeastssupporting
confidence: 67%
“…Oral taxon 066 and Oral taxon 058 tended to have lower abundances in T2 (low mask use) compared to T1 and T3 (prolonged mask use), the clinical relevance of these changes is questionable. A study by Roy et al. (2020) , investigating the effect of prolonged medical mask use on nasal and oropharyngeal microbiota through culture-based methods similarly found no changes.…”
Section: Discussionmentioning
confidence: 98%